Penatalaksanaan Fisioterapi Pada Kondisi Bell's Palsy Dextra Di RSUD Dr. Soehadi Prijonegoro Sragen - Alvionita, Mery; , Dwi Kurniawati, SST.FT, M.Kes (2015)
Background : Bell's palsy is facial abnormalities due to neurological impairment in nerve VII (the facial nerve) are located in the area of the temporal bone, around the foramen stilomastoideus happens almost always unilateral but can also be bilateral. The cause is unknown (idiopathic). Objective : To determine the physiotherapy management in improving the strength of the facial muscles and improve functional ability of facial muscles on the condition of the bell's palsy using infra red modalities, electrical stimulation (faradic) and mirrors exercise. Methods : The act modality therapy using infra red is given for 15 minutes, electrical stimulation (faradic) given for ± 20 minutes with contractions 20-30 times, and mirrors exercise to perform functional movements of the facial muscles at a dose 10 times repetition. Results : After physiotherapy for 6 times, the result is a decrease in numbness (thick), increase strength and functional ability of facial muscles and increasing the ability of functional activities such as eating, drinking and rinsing. Conclusion : Infra red, electrical stimulation (faradic) and mirrors exercise able to reduce numbness (thick), increase strength and functional ability of facial muscles and is able to improve functional activities such as eating, drinking and rinsing. Physiotherapy action can successfully perform optimally when the good cooperation between patients with a physiotherapist.